Circulating extracellular vesicles provide valuable protein, but not DNA, biomarkers in metastatic breast cancer. Issue 7 (17th July 2022) - Tkach, Mercedes; Hego, Caroline; Michel, Marc; Darrigues, Lauren; Pierga, Jean‐Yves; Bidard, François‐Clément; Théry, Clotilde; Proudhon, Charlotte
Abstract: Detection of cell‐free circulating tumour DNA (ctDNA) and cancer‐specific extracellular vesicles (EVs) in patient blood have been widely explored as non‐invasive biomarkers for cancer detection and disease follow up. However, most of the protocols used to isolate EVs co‐isolate other components and the actual value of EV‐associated markers remain unclear. To determine the optimal source of clinically‐relevant circulating biomarkers in breast cancer, we applied a size exclusion chromatography (SEC) procedure to analyse separately the content in nucleic acids of EV‐enriched and EV‐depleted fractions, in comparison to total plasma. Both cellular and mitochondrial DNA (cellDNA and mtDNA) were detected in EV‐rich and EV‐poor fractions. Analysing specific mutations identified from tumour tissues, we detected tumour‐specific cellular alleles in all SEC fractions. However, quantification of ctDNA from total plasma was more sensitive than from any SEC fractions. On the other hand, mtDNA was preferentially enriched in EV fractions from healthy donor, whereas cancer patients displayed more abundant mtDNA in total plasma, and equally distributed in all fractions. In contrast to nucleic acids, using a Multiplexed bead‐based EV‐analysis assay, we identified three surface proteins enriched in EVs from metastatic breast cancer plasma, suggesting that a small set of EV surface molecules could provide a disease signature. Our findings provide evidence that the detection of DNA within total circulating EVs does not add value as compared to the whole plasma, at least in the metastatic breast cancer patients used here. However, analysis of a subtype of EV‐associated proteins may reliably identify cancer patients. These non‐invasive biomarkers represent a promising tool for cancer diagnosis and real‐time monitoring of treatment efficacy and these results will impact the development of therapeutic approaches using EVs as targets or biomarkers of cancer.